Penguatan Kapasitas Petani Sawit dalam Menentukan Strategi Penjualan TBS yang Menguntungkan: Kasus Petani Gampong Teupin Panah Kecamatan Kaway XVI Aceh Barat - Muhammad Nasir; Syahril Syahril; Saiful Badli; Helmi Noviar; Affandi Affandi (Universitas Teuku Umar, 2026)
This community service activity was carried out with the aim of strengthening the capacity of oil palm farmers in formulating more profitable strategies for selling Fresh Fruit Bunches (FFB) in Teupin Panah Village, Kaway XVI District, West Aceh Regency. The problems faced by farmers include low FFB selling prices, high dependence on middlemen, lengthy marketing chains, and limited access to market price information. The implementation of the activity employed a participatory approach consisting of socialization, training, and direct field assistance. The materials delivered included an understanding of the FFB price formation mechanism, determining the optimal harvesting time, techniques for maintaining fruit quality, and selecting more efficient marketing channels.The results of the activity showed an improvement in farmers’ understanding of FFB selling strategies, enhanced ability to determine harvesting time and maintain harvest quality, as well as better access to and utilization of market price information. In addition, there was a behavioral change in selling activities, where farmers began comparing prices before selling, reducing dependence on middlemen, and considering direct sales to palm oil mills (POMs). Another visible impact was the increased efficiency of marketing costs and the growth of farmers’ income margins. Overall, the capacity strengthening through this activity proved effective in improving farmers’ bargaining position within the FFB marketing system and contributed to enhancing the welfare of smallholder oil palm farmers.